Eco-Pragmatic Pedagogy of Mabokuy Art: Transforming Local Wisdom as a Medium for Strengthening Ecological Literacy in the Purwaraja Community : Indonesia - Marnastiar Munsyid; Riska Sintia; Santy Rahmawati (Universitas Galuh, 2026)
This study aims to analyze Mabokuy art as a transformation of local wisdom within the framework of Eco-Pragma Pedagogy and its contribution to strengthening ecological awareness in the Purwaraja community. The research employed a qualitative method with an ethnographic approach, utilizing participatory observation, in-depth interviews, and cultural documentation. The findings reveal that Mabokuy functions not only as a bamboo-based helaran art performance but also as a form of cultural pedagogy that integrates ecological, social, and economic values in a contextual manner. The symbolism of bamboo in Mabokuy represents sustainability, harmony between humans and nature, and Sundanese cultural identity. Furthermore, collective practices in the production and performance processes serve as experiential and intergenerational learning spaces that internalize ecoliteracy through community-based social practices. This study concludes that traditional arts grounded in local wisdom possess significant potential as adaptive and sustainable non-formal ecological education models in responding to the challenges of modernization and environmental degradation.